Exploring awareness and perception on palliative care - internet as source of knowledge - Mohamadali, Noor Azizah (American Scientific Publishers, 2015)
Objective: The study aimed to assess the awareness and perception on palliative care among students in Malaysia and argues that awareness could be increased with the help of Internet Technology through various means of disseminating information to the public. Background: Understanding the level of awareness and perception of Palliative Care (PC) would be vital to ensure services and facilities provided for PC reached those in needs of services. Despite the fact that PC has been around for more than two decades in Malaysia, many are still unaware of its existence and the role it play. Method: An online and self-administered questionnaire was posted in Doctorate Support Group in Facebook to assess palliative care knowledge among the students who are currently pursuing either master or doctorate study. The study included only Malaysian students’ population. Findings: A total of 101 students participated in the survey with 62 valid responses. The majority of students, 52% (n=32) indicated that they have no knowledge in Palliative Care. Further, there is no much different in the level of awareness between student of age between 18 – 29 years and 30 years old and above. 21% (n=13) of the respondents who answered that they have knowledge on palliative care, indicated that their source of information on Palliative Care comes from social media such as Internet sources and Facebook. Interestingly, those responded that they have knowledge on Palliative care, their awareness on services offered, existence of Pediatric Palliative Care, whether services offered is free of charge etc., are shown low. Conclusion: In the age of digital, information is being shared in a matter of second all over the world. The findings from this study showed that level of awareness and knowledge on Palliative Care among students in Malaysia is still low although Palliative Care has been established for more than 20 years now. These findings hopefully will help the NGOs and government to take a more proactive approach to raise public awareness on PC through sharing and disseminating information to the public by utilizing the services provided by the Internet.